The Effect of Auditor Switching, Profit Loss And Total Assets on Audit Report Lag - Rumsiah Rumsiah; Tati Rosyati (Peneliti.net, 2022)
This study aims to determine: (1) The simultaneous effect of auditor turnover, income and total assets on audit report lag, (2) Effect of auditor turnover on audit report lag, (3) Effect of profit and loss on audit report lag, (4 ) The effect of total assets on audit report lag. The effect of auditor turnover, profit and loss and total assets on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. This type of research is a quantitative research with a causal method. Samples were taken using purposive sampling technique. The sample consists of 345 data from 69 manufacturing sector companies listed on the 2016-2020 BEI. The data analysis technique used is descriptive statistics and panel data regression using Eviews 9.0. Based on the results, it shows that auditor turnover, income and total assets simultaneously affect audit report lag, auditor turnover does not affect audit report lag, profit and loss affects audit report lag, total assets have no effect on audit report lag.